Epidermal chloroplasts are defense-related motile organelles equipped with plant immune components - Hiroki Irieda (Nature Portfolio, 2021)
Leaf epidermal cells contain small chloroplasts which likely contribute little to photosynthesis and whose function is unclear. Here the authors show that these chloroplasts move toward the leaf surface in response to invasion trials by non-adapted fungal pathogens and contribute to non-host resistance.